P104 Response of the COPD Assessment Test (CAT) to Pulmonary Rehabilitation in Non-COPD Patients. (19th November 2012) - Kon, SSC; Clark, AL; Dilaver, D; Peasey, MM; Canavan, JL; Jones, SE; Ng, MGS; Patel, MS; Polkey, MI; Man, WDC
Abstract : Background: The COPD (chronic obstructive pulmonary disease) assessment test (CAT) is a recently introduced, simple to use health status instrument, which takes less time to complete than better-established health status instruments (Jones PW et al 2009, Ringbaek T et al 2012). In COPD patients, the CAT improves with pulmonary rehabilitation (PR) and correlates with improvements in longer established health status instruments such as the Chronic Respiratory Disease Questionnaire (CRDQ) (Dodd et al 2011). As increasing numbers of non-COPD patients are referred for PR we investigated whether the CAT is responsive to PR in these populations. Methods: 365 consecutive patients (255 COPD, 110 non-COPD) completing an eight week outpatient pulmonary rehabilitation programme were recruited. For the non-COPD group, disease classifications included interstitial lung disease (n=27), asthma (n=37), bronchiectasis (n=29), extrathoracic restriction (n=12) and thoracic surgery for lung cancer (n=5). CAT, CRDQ and incremental shuttle walk (ISW) were collected prospectively. Paired t-tests were used to assess the CAT in COPD and non-COPD patients, and a Pearson's correlation coefficient used to assess the relationship between change in CAT and change in CRQ with PR for non-COPD and COPD patients. Results: Following PR there was a significant improvement in the CAT, CRDQ and ISW in both non-COPD and COPD (p<0.001). There was a similar improvement in the mean (95% confidence interval) CAT score in both non-COPD and COPD patients (non-COPD: –2.1 (–1.0, –3.2) versus COPD: –3.0 (–2.2, –3.8); p=0.19). Change in CAT was significantly correlated with all domains of the CRQ in non-COPD patients (all p<0.01 see Table 1 ). Conclusions: As in COPD patients, the CAT is immediately responsive to PR in non-COPD patients. Even in unselected patients undergoing PR, the CAT is a practical but robust health status instrument.